The Athena Doctrine - D'Antonio, Michael; Gerzema, John (Ascent Audio, 2020)
Among 64,000 people surveyed in thirteen nations, two-thirds feel the world would be a better place if men thought more like women. This marks a burgeoning global trend away from the winner-takes-all, masculine approach to getting things done. Drawing from interviews at innovative organizations in eighteen nations and at Fortune 500 boardrooms, the authors reveal how men and women alike are recognizing significant value in traits commonly associated with women, such as nurturing, cooperation, communication, and sharing. The Athena Doctrine shows why femininity is the operating system of 21st century prosperity: Leadership: values traditionally associated with women create more effective leadership and organizational strategies in todays society. Career management and self-improvement: traits associated with womenflexibility, empathy, and honestyunderpin career mobility and personal fulfillment. Change management: feminine traits help us adapt seamlessly and effectively to todays changes. Brought to life through real world portraits of women and men who lead Fortune 1000 businesses, new ventures, government and nonprofit agencies, and community groups--and backed by rigorous data--social theorist John Gerzema and author Michael D'Antonio show how traditionally feminine traits are ascending and bringing success to people and organizations around the world. By nurturing, listening, collaborating and sharing, women and men are solving problems, finding profits, and redefining success in every realm.